2017
DOI: 10.1108/tg-10-2016-0071
|View full text |Cite
|
Sign up to set email alerts
|

Does social media transform city government? A case study of three ASEAN cities

Abstract: Purpose -This research aims to investigate the impact of the use of social media on the organizational form and function in selected local governments of Indonesia, Thailand and the Philippines.Design/methodology/approach -This research used quantitative and qualitative methods. The researchers not only conducted comparative-explanatory studies among the three ASEAN cities but also used multiple-informant and secondary data analyses. All variables are operationalized into indicators and transformed into a ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 64 publications
1
17
0
1
Order By: Relevance
“…For example, now public can easily access government accountability performance reports (LAKIP) and various types of government performance reports through the official government website. Also, government official of all levels have activated official government social media accounts, to facilitate the process of interaction between the society and the government [25].…”
Section: A the Phenomenon Of Public Criticism On The Government's Acmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, now public can easily access government accountability performance reports (LAKIP) and various types of government performance reports through the official government website. Also, government official of all levels have activated official government social media accounts, to facilitate the process of interaction between the society and the government [25].…”
Section: A the Phenomenon Of Public Criticism On The Government's Acmentioning
confidence: 99%
“…In the Industry 4.0 era, there is one technology that can be offered to gather the different views and help to reach a consensus on the matters discussed on social media in realtime and quickly. The technology is the big data application for social media analytics which has been implemented in several major cities in Indonesia, such as Jakarta, Bandung, and Makassar [25]. Unfortunately, the accountability of the government's social media analytics app implementation is still difficult to be accessed by the public and currently no clear standards for the local governments' online accountability.…”
Section: A Suggestion From the Science And Technological Approachmentioning
confidence: 99%
“…Th is is similar to fi ndings on FB use that was summarized as using new tools in a traditional, rather than a more innovative way (see the fi ndings of Hofmann et al 2013 summarized above) -e.g. to the fi ndings of Bonsón et al (2015) (who concentrated on municipalities of Western European states), Gunawong (2015) and Roengtam et al (2017) (who concentrated on Th ailand or ASEAN cities), to observations in the US (as outlined above) as well as to researched practices in Australia (e.g. Khayiri et al 2014).…”
Section: Figurementioning
confidence: 99%
“…Social media has become an alternative Internet solution for all Filipino online users. But Scholars [11] has revealed that social media can hinder rather than facilitate the delivery of goods and services. Statistically, the Internet population in the Philippines is made up of 80% of social media users, such as Facebook, Twitter, Tumbler and Pinterest.…”
Section: Introductionmentioning
confidence: 99%